Tanggungjawab Pengurus Dalam Pengelolaan Primer Koperasi Produsen Tempe Tahu Indonesia (PRIMKOPTI) Di Kabupaten Karanganyar - Adisurya, Whisnu Anggoro; , Inayah, S.H, M.H (2017)
This study aims to determine the functions, benefits and problems arising in the administration as well as to determine the management system entity Tofu Tempe Producers Cooperative Primer Indonesia (PRIMKOPTI) in Karanganyar. This research used juridical empirical approach is descriptive. Source of data derived from primary data, interviews and secondary data as the data source of primary law, secondary and tertiary. Data were collected by interview, then analyzed using qualitative analysis methods. The results showed that the functions and benefits for members PRIMKOPTI be good, because the members more efficient in its performance and is able to compete with other soy craftsmen. Rights and obligations of well executed by the board in the management of PRIMKOPTI are looking for soy and distribute to members. The role of the Department of Cooperatives in the supervision and management of Primkopti that is doing the controlling and evaluation of the Micro, Small and Medium Enterprises in Karanganyar properly and correctly in accordance with the principles of cooperatives and the cooperative principles.